Design and experiment of variable rate orchard sprayer based on laser scanning sensor - Li, Longlong; He, Xiongkui; Song, Jianli; Liu, Yajia; Zeng, Aijun; Liu, Yang; Liu, Chaohui; Liu, Zhixiong (International Journal of Agricultural and Biological Engineering, 2018)
During different growth periods, canopy size and density in orchards are variable, which need application conditions (flow rate and air flow) to be adjusted to match the canopy’s characteristics. In order to improve orchard sprayer’s automatic operating performance, an automatic variable-rate orchard sprayer (VARS) fixed with 40 electromagnetic valves and 8 brushless fans was developed based on the canopy’s spatial dimensions. Each solenoid valve and brushless motor can be individually adjusted in real-time through pulse width modulation (PWM) signals emitted by a control system to adjust each nozzle’s spout and fan rotation speed. A high-precision laser scanning sensor (light detecting and ranging, LIDAR) was adopted as the detector to measure the canopy volume using the variable rate algorithm principle. Field experiments were conducted in an apple orchard, and conventional air blast sprayer (CABS) and directed air-jet sprayer (DAJS) were tested as a comparison. Results showed that on average, 46% less spraying solution was applied compared to conventional applications, while penetration rate was similar to DAJS. Normalized deposition in the canopy with variable application was higher than that of conventional applications, indicating that electronic sprayers are more efficient than conventional sprayers. It was also observed that VARS could significantly reduce off-target loss. The field experiment showed that the newly developed variable-rate sprayer can greatly reduce pesticide use and protect the environment for the orchard fruit production, and also provide a reference for design and performance optimization for plant protection machinery. Keywords: variable rate, orchard, sprayer, spatial dimension, air volume, flow rate, laser scanning sensor, precision agriculture DOI: 10.25165/j.ijabe.20181101.3183 Citation: Li L L, He X K, Song J L, Liu Y J, Zeng A J, Liu Y, et al. Design and experiment of variable rate orchard sprayer based on laser scanning sensor. Int J Agric & Biol Eng, 2018; 11(1): 101–108.